Analisis Pengaruh Pengukuran Potensi Kebangkrutan Metode Altman Z-Score, Zmijewski X-Score dan Springate S-Score Terhadap Harga Saham pada Perusahaan Subsektor Media dan Hiburan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Kurnia Sari Dewi; Rousilita Suhendah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the effect of bankruptcy potential measurement methods namely the Altman Z-Score, Zmijewski X-Score, and Springate S-Score on stock prices. The study utilizes secondary data obtained from media and entertainment subsector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research sample was selected using a purposive sampling method, comprising 12 companies with a total of 48 observations. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM), processed using EViews 12 software. The results indicate that the Altman Z-Score has no effect on stock prices, the Zmijewski X-Score does not have a significant positive effect on stock prices, while the Springate S-Score has a significant positive effect on stock prices. These findings suggest that the Altman Z-Score and Zmijewski X-Score are less relevant in predicting market reactions to a company’s fundamental conditions.